(3TQM efXheI GdYQGbi aj GdhVhAs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s; (3Rjf GdOjf YHO GdQMje GdYQGbjs ((3eMeO Hf GdMSf GdHGHi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi abO hbaJ dhGdOj CHbGg Gddg Ydi fXe LeY ajg bjO GdUhQ GdJj bjd ajgG HESJMHGH GdhVhA ajgG aQCjJ TQMgG s
(3BNQgG (B:s
(3GdJGSYI hGdKdGKhf GdZVH PcQg ai TQM GdegPH hde jPcQg ai GdfXe ESJZfGA Yfg HeG PcQg ai GdeSH hddeSH GdeNJda ai GdfbV Hg hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH Je TQM GdGHjGJ GdePchQI s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf s
Keywords: (3GdMOjK h GdeUWdMs